1981
DOI: 10.1126/science.211.4483.705
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis: A Response to Low Environmental Concentrations of Petroleum Hydrocarbons

Abstract: Crab zoeae ( Rhithropanopeus harrisii ) were exposed to water-soluble fractions of jet fuel (JP5) for the first 5 days or for the duration of zoeal development (11 to 14 days). Short-term exposure or continuous exposure to low concentrations of petroleum hydrocarbons caused no increase in mortality or changes in development rate, and increased megalopal weight was characteristic of such groups. This phenomenon, termed "hormesis," is probably a generalized aspect of environmental stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 9 publications
3
33
0
Order By: Relevance
“…Survival following sublethal exposures of invertebrates varies based on species and life stage [21,54,62,63]. In the present study, F. duorarum nauplii exposed to sub-lethal amounts (23 mg L´1, LC 10 ) of CEWAFs for 24 h showed no difference in survival compared to controls over 39 days and was approximately 25% for both groups.…”
Section: Sublethal Effectsmentioning
confidence: 63%
See 3 more Smart Citations
“…Survival following sublethal exposures of invertebrates varies based on species and life stage [21,54,62,63]. In the present study, F. duorarum nauplii exposed to sub-lethal amounts (23 mg L´1, LC 10 ) of CEWAFs for 24 h showed no difference in survival compared to controls over 39 days and was approximately 25% for both groups.…”
Section: Sublethal Effectsmentioning
confidence: 63%
“…Delayed morality has been reported by other researchers in shrimp and crab larvae and embryos exposed to low levels of WSF for short periods with zoea being more sensitive than later developmental stages [21,54,62]. Other research has shown no survival effects in crab zoea following either short term exposure or continuous exposure to low concentrations of oil [63].…”
Section: Sublethal Effectsmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, a reduction in growth is generally considered an adverse effect; but what if growth increases in response to contaminant exposure? Enhancement of a physiological process by exposure to low levels of contaminants is known as the Arndt-Schulz effect, "sufficient challenge," or hormesis (Laughlin, Ng, and Guard 1981). This effect is well documented (Stebbing 1981;Sanders, Laughlin, and Costlow 1984;Laughlin, Ng, and Guard 1981;Weis and Weis 1986) and is attributed to short-term overcompensation of homeostatic regulatory control mechanisms to an external challenge.…”
Section: Discussionmentioning
confidence: 99%